Análise do processo de higienização pré-operacional com detergente enzimático em tubulações de um abatedouro de aves - Silva Junior, Adaelson Firmino da (2022)
Brazil is one of the largest producers and occupies a prominent position in exports of chicken meat. Therefore, it is essential that the poultry industry monitors the health risks that its products can pose to consumers. Bacterial dissemination is possible to occur at all stages of the process and tends to isolate in places inaccessible to conventional hygienic methods. Ineffective sanitation can result in the formation of biofilms, which can lead to difficult removal and increased resistance. The eviscerated poultry product line, where the liver production line stands out, is a critical stage and can have its sanitation improved through the use of enzymatic detergents preventing the formation of biofilms. The objective of this study was to analyze the pre-operational cleaning process with the use of chlorinated detergent only, with the inclusion of enzymatic detergent, and finally with the inclusion of an exclusive CIP (clean-in-place) line implemented for evaluation. The samples were collected in three moments: 0 (before hygienization); 1 (after the first hygienization at the end of the week's production), and 2 (after a second hygienization with the weekend break without production) in 6 points: CF0, CF1 and CF2 (chuter-receiving liver); and TF0, TF1 and TF2 (tubing). A visual biofilm developer was used to verify the presence of biofilms, and as for the presence of microorganisms, microbiological analyses were performed (Aerobic mesophiles, Enterobacteriaceae, Listeria monocytogenes, Salmonella spp) with the samples being collected through swabs at strategic points in the pipeline. Physicochemical analyses of such as pH, chlorine and turbidity of the water were also performed. The results revealed that the treatment adding the enzymatic detergent to the sanitizing process still showed the presence of biofilm, even after the second sanitizing. The statistical results showed that for the data of aerobic mesophiles and Enterobacteria count and pH, chlorine and turbidity when evaluated on the employed CIP treatment (chlorinated detergent, enzymatic detergent and associated) in no way differ from each other in the time observed from the first operational cleaning to the last, regardless of treatment. Regarding biofilm, there was a significant difference, being more effective when there was an association of the CIP system with chlorinated and enzymatic detergent. In this sense, this work adds great value to the company by bringing practical answers for the improvement of the Standard Sanitizing Operating Procedures (SSOP).